European Commission Guidelines for the prudent use of antimicrobials in human health: a missed opportunity to embrace nursing participation in stewardship - Castro,Sanchez EM; Bennasar-Veny,M; Smith,M; Singleton,S; Bennett,E; Appleton,J; Hamilton,N; McEwen,J; Gallagher,R (Clinical Microbiology and Infection, 2018)
Our letter highlights the shortcomings of recent EU Commission Guidelines for the prudent use of antimicrobials in human health in terms of the contribution of nurses towards stewardship. Such contribution has been advocated much more progressively in recent documents, which have also expanded the domains of the contribution to include domains other than clinical.